Development of NbTi planar superconducting undulators at the IHEP - Wei, Junhao; Yang, Xiangchen; Chen, Zilin; Zhang, Xiangzhen; Bian, Xiaojuan; Li, Yuhui (Frontiers in Physics, 2023)
Superconducting undulators have the ability in generating higher peak field compared to the cryogenic permanent magnet undulators with the same period length (>15 mm) and vacuum gap. Another advantage of SCUs with respect to PMUs is the radiation hardness which is an important issue for free-electron lasers (FELs) driven by high repetition rate linear accelerators. The above advantages make SCUs attractive to be deployed in continues-wave (CW) FELs. The insert device group at the institute of high energy physics (IHEP) in China started an R&D project to produce NbTi planar SCU prototypes. The prototypes are designed based on the simulation programs with a period length of 15 mm. The SCU mock-up coils were quench trained at 4 K to reach the best current load capacity. Several SCU prototypes including short mock-ups, a 0.5-m-long SCU and a 1.5-m-long SCU have been successfully produced and tested. After the quench training, the SCU achieved the ability in loading high current. The magnetic field measurement results from the vertical test system indicated the good field quality of the SCU prototypes. This paper will introduce the development of the SCUs at the IHEP in detail.